Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina - Roig-Alsina, Arturo; Alvarez, Leopoldo J. (Zootaxa, 2017)
The southern distribution of stingless bees in the Neotropics reaches the province of Buenos Aires, Argentina, up to 34°51' S in latitude, where two species of Plebeia are found on the west margin of the Río de La Plata: P. emerinoides (Silvestri), and P. droryana (Friese). In this area some relicts of gallery forest occur and the climate is moderated by the large water mass of the river. The taxonomy of both species is discussed. Diagnoses, updated distribution, and illustrations of some morphological features are given for both species.